2004
DOI: 10.1016/j.jcrs.2003.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Correction of presbyopia with refractive multifocal phakic intraocular lenses

Abstract: Implantation of an anterior chamber multifocal phakic IOL to correct presbyopia was effective and gave good predictability. The procedure is reversible in cases of patient intolerance to the IOL, unwanted optical phenomena, or complications. Strict inclusion criteria should be used for patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 12 publications
0
26
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8] The ReSTOR IOL recently became commercially available in some countries. Studies report this IOL provides good near visual acuity and distance correction with negligible side effects (F. Carones, ''Visual Performance of the AcrySof Our study also found that the results of uncorrected distance visual acuity and uncorrected near visual acuity in eyes with the ReSTOR IOL were satisfactory, with 92% and 89%, respectively, obtaining an acuity of 20/30 or better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] The ReSTOR IOL recently became commercially available in some countries. Studies report this IOL provides good near visual acuity and distance correction with negligible side effects (F. Carones, ''Visual Performance of the AcrySof Our study also found that the results of uncorrected distance visual acuity and uncorrected near visual acuity in eyes with the ReSTOR IOL were satisfactory, with 92% and 89%, respectively, obtaining an acuity of 20/30 or better.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The quality of vision with the earlier multifocal IOLs models is good, and subjective satisfaction with multifocal IOLs is superior to that with monofocal IOLs. 1,2 However, some patients with early model multifocal IOLs complained of changes in visual clarity at different distances.…”
mentioning
confidence: 99%
“…After multifocal IOL implantation 22,24-26 many patients report an increase in halos. 23 Regarding these optical side effects, we would like to cite a recent statement of Baïkoff et al 27 : ''Optical defects are inevitable with multifocal IOLs..'' Although this argument holds mainly for a cornea that has a clearly multifocal CSI shape, a similar loss in contrast sensitivity is expected with strongly aspherical corneas. However, an asphericity constant Q of À0.7, as intended in the GO, is only À0.5 away from the mean 28 and compares favorably with the up to 3 times larger changes in the asphericity constant after standard myopic laser in situ keratomileusis of up to C1.50 D. 29,30 Also, emmetropic or hyperopic eyes receiving a hyperopia correction for attempted slight myopia for monovision experience a shift in asphericity toward prolate of approximately À0.50 D. 31 The most frequent presbyopia correction is the monovision approach, in which the dominant eye is corrected for emmetropia and the nondominant eye for mild myopia ranging from À0.50 D to À2.00 D. [32][33][34][35][36] In clinical surgery practice, the optimum configuration is tested for patient satisfaction before surgery using contact lenses.…”
Section: Discussionmentioning
confidence: 99%
“…Novos modelos de lentes multifocais intra-oculares estão disponíveis e poucos estudos relatam os resultados de lentes fácicas multifocais para a correção da presbiopia (11)(12) . De uma maneira geral, os resultados apresentados no presente estudo concordam com os relatos previamente publicados sobre resultados refrativos com cirurgia de implante de lentes fácicas (2)(3)6,12) .…”
Section: Discussionunclassified
“…Além disso, o índice de retirada da lente intraocular também foi maior que previamente descrito (11) . A maior causa da retirada da lente foi a catarata (3 de 51 olhos apresentaram catarata).…”
Section: Discussionunclassified